Creating Memories and Engagement in College Student Through Virtual Reality - Loureiro, S. M. C.; Bilro, R.G.; Angelino, F. J. (6th International AR VR Conference, 2020)
This study intends to extend the understanding of drivers of student engagement in the educational context and analyse mindfulness as a moderator of the different associations in the proposed model. The proposed model regards VR experiences as stimuli, telepresence, pleasantness of the experience and memory as an organism and student engagement as the response. A sample of 136 participants allowed us to test the model. Findings revealed that all hypotheses were supported except H6 linking pleasantness of the experience with student engagement. Only the relationship between pleasantness and memory is higher for mindful students than non-mindful ones. These findings mean that students do not need to feel pleasure about what they are learning to be engaged.